Gendang Melayu Sarawak (GMS) – Sarawak Malay Drum, the dying and forgotten tradition - Sinin, Aaliyawani E.; Hamdan, Sinin; Mohamad Said, Khairul A.; Abdullah, Santrol; Musib, Ahmad F. (North Carolina State University, 2024)
This work was conducted using the Picoscope signal extraction procedure, which revealed significant insights regarding the belian wood and its application in Gendang Melayu Sarawak (GMS) production. The amplitude of belian wood GMS signal remains constant, allowing it to sustain its timbre for a longer duration compared to durian wood GMS using the same procedure. Considering that the dimensions of the big belian (BB) and big durian (BD) GMS are almost the same, both GMS yield almost the same note, i.e. G1#(51.9 Hz). Considering that the dimensions of both the small belian (SB) and small durian (SD) GMS are almost the same, both GMS yield almost similar note, i.e. F3 (174 Hz) and E3 (164 Hz). Although both BB and BD showed consistent harmonics, BD only displays 2 harmonics. The SB and SD both display consistent harmonics. Both BB and BD showed pleasing tonal qualities. These occurred due to the closeness of the principal overtones to the consonant interval. © 2024, North Carolina State University. All rights reserved.